The information-motivation-behavioral skills model explains physical activity levels for adults with type 2 diabetes across all weight classes. Issue 3 (16th March 2021) - Ferrari, Madeleine; Speight, Jane; Beath, Alissa; Browne, Jessica L.; Mosely, Kylie
ABSTRACT: Physical activity is an evidence-based, effective treatment for type 2 diabetes mellitus (T2D), yet insufficient numbers of adults achieve recommended daily levels, particularly amongst higher weight classes. This cross-sectional study assessed whether the Information-Motivation-Behavioural Skills (IMB) Model explained physical activity levels in adults with T2D across different body mass index (BMI) levels (N = 381). Measures included the American Adults Knowledge of Exercise Recommendations (AAKER), Behavioural Regulation in Exercise Questionnaire (BREQ-2), Barriers Specific Self-Efficacy Scale (BARSE) and the outcome measure, International Physical Activity Questionnaire (IPAQ-short form). Analyses included structural equation modelling (SEM) and ordinal logistic regression models. SEM demonstrated a good fit of the IMB Model to the data, accounting for 44% of variance in physical activity levels. Both motivation and self-efficacy had a direct effect, and motivation indirectly predicted physical activity through self-efficacy. Further analyses found the effect of the IMB predictors did not vary according to BMI status. This study supports the application of the IMB Model in explaining physical activity behavior in adults with T2D. In particular, the contribution of motivation and self-efficacy as substantive and modifiable predictors of physical activity will facilitate the development of targeted and evidence-based interventions for individuals of all BMI classes.